IMPLEMENTING TASK–BASED LANGUAGE TEACHING THROUGH PICTURE SERIES TO IMPROVE RECOUNT TEXT WRITING - Sumini Sumini; Y. Gatot Sutapa; Regina Regina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe purpose of this research was to improve students’ recount text writing of  the eighth grade at SMPK Filadelfia Sadaniang Mempawah regency in the academic year of 2017-2018. This Classroom Action Research  was conducted Task–Based Language Teaching through picture series. It was conducted at SMPK Filadelfia Sadaniang Mempawah regency and involved of 15 students in grade VIII. The researcher employed Jane Willis (1996). Task–Based Language Teaching (TBLT) framework which consisted of Pre-task, Task cycle, and Language focus. The data collections used in this research were the students’ involvement and students’ writing results in two cycles. The procedures included planning, implementing/acting, observing, and reflecting. The result shown that the application of Task–Based Language Teaching (TBLT) framework to teach recount text writing through picture series could successfully improve students’ ability in writing. The finding also reveal that Task–Based Language Teaching (TBLT) through picture series gave positive attitude to the students.Keywords: Implementing Task–Based Language Teaching, Picture Series, Recount                 Text Writing